Senescence across multicellular organisms, with a focus on social species - Roper, M (2022)
Senescence, the increasing risk of mortality and/or decreasing rate of reproductive success, is, at first glance, detrimental to individual fitness. Developments in evolutionary theory for senescence across the 20th century, however, suggested that despite its detrimental effects, senescence is an inevitable outcome of evolution. The variable patterns of age-specific mortality and reproduction observed in nature suggest otherwise. In this thesis, I explore the variation in senescence across multicelluar organisms, with a particular focus on social species. Specifically, I: (i) review the current state of theoretical and empirical senescence research, suggesting evolutionary explanations for the variation in age-specific mortality and reproduction observed across species; (ii) quantify levels of covariation between metrics of actuarial (mortality) and reproductive ageing; (iii) model how social interactions between individuals might modulate ageing and senescence; (iv) comparatively test predictions of the model in social species; and (v) test for senescence in a wild population of a cooperative breeder. Overall, I suggest that the force of selection is still integral to understanding the evolution of senescence. The force of selection, introduced by Hamilton (1966), allows for the quantification of how strongly a detrimental allele will be selected against as a function of the age at which the allele invades. Hamilton’s results suggested that the force of selection is always a monotonically declining function with increasing organism age. By breaking assumptions from Hamilton’s model, however, we can observe forces of selection that need not always decline with age, and thus better predict the diversity of ageing patterns observed in nature.